2009
DOI: 10.1165/rcmb.2008-0300oc
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase in Bone Marrow–Derived Cells Mediates Pulmonary Ischemia-Reperfusion Injury

Abstract: Reactive oxygen species (ROS) play a crucial role in ischemiareperfusion (IR) injury after lung transplantation. We hypothesized that NADPH oxidase derived from bone marrow (BM) cells contributes importantly to lung IR injury. An in vivo mouse model of lung IR injury was employed. Wild-type C57BL/6 (WT) mice, p47 phox knockout (p47 phox 2/2) mice, or chimeras created by BM transplantation between WT and p47 phox 2/2 mice were assigned to either Sham (left thoracotomy) or six study groups that underwent IR (1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 33 publications
3
60
1
Order By: Relevance
“…Use of apocynin blocks MAPK signal transduction and attenuates apoptotic cell death by blocking intrinsic and extrinsic signaling pathways during ischemia and reperfusion injury [30][31][32][33][34][35][36][37]. Several studies [21,38,39] have shown organ protective effects of apocynin by inhibition of cyclooxygenase metabolites in a variety of animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Use of apocynin blocks MAPK signal transduction and attenuates apoptotic cell death by blocking intrinsic and extrinsic signaling pathways during ischemia and reperfusion injury [30][31][32][33][34][35][36][37]. Several studies [21,38,39] have shown organ protective effects of apocynin by inhibition of cyclooxygenase metabolites in a variety of animal models.…”
Section: Discussionmentioning
confidence: 99%
“…phox knockout mice, wildtype mice, and chimeras created by bone marrow transplantation indicate that NOX-generated ROS, specifically from bone marrow-derived cells, contribute to lung ischemia= reperfusion injury (148). Furthermore, recent studies indicate that activation of an EC-associated NOX may be the primary mechanism for ROS generation during reoxygenation after lung ischemia (5,152).…”
Section: Nox Enzymes In Obstructive Sleep Apnea and Ischemia/reperfusionmentioning
confidence: 99%
“…neutrophil/mononuclear phagocyte activation and infiltration) (30), and proinflammatory cytokines and chemokines (7,8,15,20,24), all exemplifying multiple complex inflammatory pathways involved in PGD.…”
Section: Introductionmentioning
confidence: 99%